Analysis of Influence Factors on the Quality of International Collaboration Research in the Field of Social Sciences and Humanities: The Case of Chinese World Class Universities (2015–2019). (October 2021) - Zhe, Cheng; Lu, Xingfu; Xiong, Xiong
This article aims to reveal the factors that affecting the impact of international collaboration papers in the field of social sciences and humanities. Based on resource-based theory and transaction cost theory, we analyzed the articles from a sample of 13, 331 listed research papers come from the 42 world class universities in China using descriptive statistics, ordinary least square (OLS) regression, and came to the following conclusions: First, it is the quality rather than the quantity of international collaborator that affect the academic influence of the research outputs. Second, researchers from different backgrounds are conducive to improve the impact of research papers and the collaboration leading by Chinese university perform better. Yet, too much collaborators coming from different institutions would have an adverse impact, which may due to the increase cost of cooperation. Finally, collaborating researchers from developed countries or top universities will significantly improve the research performance because of the abundant resources behind them. Findings from this research suggest that setting up international collaboration should pay more attention to the level of the collaborator and consider the cost behind the whole process.